Percutaneous and Open Retrograde Endovascular Stenting of Symptomatic High-Grade Innominate Artery Stenosis: Technique and Follow-Up - Mordasini, P.; Gralla, J.; Do, D.-D.; Schmidli, J.; Keserü, B.; Arnold, M.; Fischer, U.; Schroth, G.; Brekenfeld, C. (American Journal of Neuroradiology, 2011)
BACKGROUND AND PURPOSE: Angioplasty and stenting of the IA have been reported with high technical and clinical success rates, low complication rates and good mid-term patency rates. Different antegrade or retrograde endovascular catheter-based approaches and combinations with surgical exposure of the CCA are used. The purpose of this study was to determine safety, efficacy and mid-term clinical and radiological outcome of the stent-assisted treatment of atherosclerotic stenotic disease of the IA with special focus on the different technical approaches. MATERIALS AND METHODS: Between 1996 and 2008, 18 patients (12 men, 6 women) with symptomatic high-grade stenosis (>80%) of the IA were treated with endovascular stent placement. Their mean age was 60.4 years (range, 48–78 years). Mean angiographic and clinical follow-up was 2.7 years (range, 0.3–9.1 years). Clinical follow-up was performed by using the mRS at hospital discharge, routine follow-up controls, and a questionnaire. In 11 patients, a percutaneous approach was used. In 7 patients, the lesions were accessed retrogradely through a cervical cut-down with common carotid arteriotomy. In 2 patients, a simultaneous ipsilateral carotid endarterectomy was performed. RESULTS: In all patients, primary stent placement was performed. There were 2 procedure-related transient complications (11.1%) due to cerebral embolism without permanent morbidity or mortality. During the follow-up, all patients showed improvement of the preprocedural symptoms. At the latest clinical follow-up (mean, 2.7 years), all patients showed an excellent or good outcome (mRS, 0 or 1). In 2 patients (11.1%), a secondary stent placement was needed due to a significant symptomatic in-stent stenosis. CONCLUSIONS: Percutaneous and open retrograde stenting of high-grade stenosis of the IA is a viable less invasive alternatives to open bypass surgery with good midterm clinical results and patency rates. CCAcommon carotid arteryCEAcarotid endarterectomyCTACT angiographyDSAdigital subtraction angiographyDWIdiffusion-weighted imagingIAinnominate arteryMRAMR angiographymRSmodified Rankin ScalePTApercutaneous transarterial angioplastySCAsubclavian artery